Transient stability analysis of one special type of AC microgrids with a gas reciprocating generator unit. Issue 16 (29th November 2018) - Jun, Liu; Hui‐wen, Sun; Can, Su; Jun‐hui, Wu; Gui‐quan, Han; Jian, He
Abstract : More and more gas reciprocating generator units are integrated into offshore platforms, due to their compact structure and high efficiency. This paper concentrates on the transient stability analysis of one special type of AC microgrids containing a gas reciprocating generator unit. Firstly, the operation principle for the gas reciprocating generator unit is presented, which mainly consists of a reciprocating internal combustion engine and a linear synchronous alternator (LSA). Afterwards, the mathematical model for the core part of the gas reciprocating generator unit LSA is proposed, based on the principle of armature reaction in traditional synchronous and asynchronous machines. Finally, the simplified model of the independent offshore power system with a gas reciprocating generator unit is derived, and numerical simulations on the transient stability of this typical AC microgrid are performed, from which the effectiveness and correctness of the LSA model are validated. The transient stability analysis method of the independent offshore power system and the mathematical model of LSA can provide beneficial guidance for the stable operation of other types of stand‐alone AC microgrids.